FOUR CARDINAL POINTS ON THE UNIVERSITY ACCREDITATION SYSTEM - Flores Barboza, José (2014)
In August this year, Jorge González, an outstanding Mexican professor, visited Lima invited by the National Assembly of Rectors to participate in the Seminar on selfassessment and accreditation of Higher Education. In the nineties González developed the Model of Structural Analysis of Universities, a tool used in Latin America to promote excellence in the academic and professional fields. Dr González kindly shared with us his ideas on four fundamental subjects: